2017
DOI: 10.1111/cdev.12767
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Among Children's Negative Family Representations, Visual Processing of Negative Emotions, and Externalizing Symptoms

Abstract: This study examined the transactional interplay among children's negative family representations, visual processing of negative emotions, and externalizing symptoms in a sample of 243 preschool children (M = 4.60 years). Children participated in three annual measurement occasions. Cross-lagged autoregressive models were conducted with multimethod, multi-informant data to identify mediational pathways. Consistent with schema-based top-down models, negative family representations were associated with attention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 74 publications
(112 reference statements)
0
14
0
Order By: Relevance
“…These changes in negative family representations, in turn, were associated with increases and more modest reductions in externalizing symptoms across a 2-year period. In support of this mediational link, previous research has demonstrated that negative family representations concurrently and longitudinally predict children’s externalizing problems (Davies et al, 2018; Stadelmann et al, 2007; Wagner et al, 2015). Thus, in accord with life history theory, appraisals of their primary social worlds (i.e., the family unit) as undermining safety and social cohesion may canalize children into a life history strategy that progressively coalesces into defiance, exploitation, antagonism, and impulsivity (Del Giudice, 2016).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…These changes in negative family representations, in turn, were associated with increases and more modest reductions in externalizing symptoms across a 2-year period. In support of this mediational link, previous research has demonstrated that negative family representations concurrently and longitudinally predict children’s externalizing problems (Davies et al, 2018; Stadelmann et al, 2007; Wagner et al, 2015). Thus, in accord with life history theory, appraisals of their primary social worlds (i.e., the family unit) as undermining safety and social cohesion may canalize children into a life history strategy that progressively coalesces into defiance, exploitation, antagonism, and impulsivity (Del Giudice, 2016).…”
Section: Discussionmentioning
confidence: 78%
“…family representations concurrently and longitudinally predict children's externalizing problems (Davies et al, 2018;Stadelmann et al, 2007;Wagner et al, 2015). Thus, in accord with life history theory, appraisals of their primary social worlds (i.e., the family unit) as undermining safety and social cohesion may canalize children into a life history strategy that progressively coalesces into defiance, exploitation, antagonism, and impulsivity (Del Giudice, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, two studies have also shown evidence for defensive exclusion. Specifically, as a proposed indicator of emotional insecurity in the family, children's negative cognitive representations of the family predicted subsequent decreases in children's duration of attention to anger; those decreases, in turn, predicted increases in externalizing symptoms (Davies, Coe, Hentges, Sturge-Apple, & van der Kloet, 2018). In another study, decreases in children's behavioral indices of emotional security in the interparental subsystem over a 1-year period were associated with concomitant decreases in their duration of attention to anger .…”
Section: Introductionmentioning
confidence: 95%